3D-Printed PEEK Extravascular Stent in the Treatment of Nutcracker Syndrome: Imaging Evaluation and Short-Term Clinical Outcome - He, Dali; Liang, Jiahe; Wang, Hengen; Jiao, Yong; Wu, Bin; Cui, Dong; Cao, Tiesheng; Li, Yanyan; Wang, Jing; Zhang, Bo (Frontiers in Bioengineering and Biotechnology, 2020)
Minimally invasive options are safe and reliable alternatives for the treatment of nutcracker syndrome (NCS). After continued efforts, our team successfully devised a new and effective therapeutic method: 3D-printed extravascular stenting of the left renal vein. From December 2017 to May 2019, 28 patients (25 men and 3 women) from different parts of China between 18 and 37 years old (mean, 23.6 years) diagnosed with NCS were admitted for laparoscopic 3D-printed extravascular stenting treatment. The post-operative follow-up duration was 6–24 months (median, 16.3 months). Technical success of the operation was achieved in all patients. After treatment, the NCS symptoms all patients resolved or improved during the follow-up period, without relapse. Most symptoms, including macro-/microhematuria, proteinuria, and flank/abdominal pain, tended to resolve within 3–6 months after the surgery; other symptoms, such as left-sided varicocele, also showed varying degrees of improvement at different times post-operatively. Perioperative complications were noted in two patients, including transient and mild lymphatic leakage, without any adverse effects. All extravascular stents were visualized on computed tomography and Doppler ultrasound scans, and no migration or any side effects occurred during the entire follow-up period. Compared to endovascular stenting or polytetrafluoroethylene artificial vessel procedures, 3D-printed polyetheretherketone extravascular stenting has more advantages in terms of stent design and rigidity and approach rationality while successfully preventing stent migration and thrombosis. Therefore, this method may serve as an accurate and effective treatment for NCS patients.